2020
DOI: 10.1038/s41598-020-69358-4
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell mass cytometry on peripheral blood identifies immune cell subsets associated with primary biliary cholangitis

Abstract: The relationship between primary biliary cholangitis (PBC), a chronic cholestatic autoimmune liver disease, and the peripheral immune system remains to be fully understood. Herein, we performed the first mass cytometry (CyTOF)-based, immunophenotyping analysis of the peripheral immune system in PBC at single-cell resolution. CyTOF was performed on peripheral blood mononuclear cells (PBMCs) from PBC patients (n = 33) and age-/sex-matched healthy controls (n = 33) to obtain immune cell abundance and marker expre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 42 publications
1
14
0
Order By: Relevance
“…The change in the quantity of circulating γδ T cells in PBC patients remains controversial in previous studies [9][10][11][12]. Studies have found a signi cantly decreased frequency of circulating γδ T cells in PBC patients compared with HCs [11,12], whereas the other two studies showed a similar frequency of γδ T cells between the two groups [9,10].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The change in the quantity of circulating γδ T cells in PBC patients remains controversial in previous studies [9][10][11][12]. Studies have found a signi cantly decreased frequency of circulating γδ T cells in PBC patients compared with HCs [11,12], whereas the other two studies showed a similar frequency of γδ T cells between the two groups [9,10].…”
Section: Discussionmentioning
confidence: 96%
“…Previous studies have demonstrated that γδ T cells are closely involved in the development of viral hepatitis and autoimmune liver diseases [5,8,9]. However, the frequency of γδ T cells in PBC remains controversial in previous studies with small sample sizes [9][10][11][12]. The function of γδ T cells in PBC also needs to be further explored.…”
Section: Introductionmentioning
confidence: 99%
“…Instead, proinflammatory cytokines such as IL-6 and IL-12 were produced and CD4 T cell differentiation towards a Th1 phenotype occurred (101). However, other studies have not detected differences in circulating B regulatory cells in PBC (73) and a recent analysis of immune cells at the single cell level found a different population of regulatory B cells with a B10 phenotype (high CD24 and IgD expression) were decreased rather than increased in PBC patients (98). Together these results suggest the role of different B cell subsets in PBC pathogenesis is likely to be nuanced, and dependent on the fine tuning of pro-and anti-inflammatory cytokines.…”
Section: Cytokines Regulating Inflammation and Recruitment In Pbcmentioning
confidence: 98%
“…Studies of circulating lymphocytes in PBC have observed increases in CD19+ B cells and activated CD25+ B cells, correlating with disease stage (73,97). Within the B cell compartment, different B cells subsets seem to be altered including decreased circulating memory B cells and increased naïve B cells and PBs (73,98). In liver biopsy specimens from individuals with PBC, CD20+ B cells were found in lymphoid follicle like aggregations a distance from portal tracts, or more scantily as part of the lymphoplasmacytic infiltrate surrounding inflamed bile ducts.…”
Section: B Cell Expansion and Activation In Pbcmentioning
confidence: 99%
“…On the other hand, the maximal acquisition capacity of CyTOF devices is limited to 1000 cells/s [5] , while a rate of 400 cells/s is recommended to avoid cell aggregation and doublet formation [6] , [7] . Because of this, it becomes problematic to acquire multiple samples per day, particularly if several tubes of complex tissues (like blood or liquid biopsies) are acquired to detect rare cell populations.…”
Section: Introductionmentioning
confidence: 99%